STUDY OF THE DIGESTIVE CAPACITY OF THE STOMACH BY MEANS OF PHYSIOCHEMICAL METHODS I - LACHIES, ALBERTO DE; CYTRONBERG SEWERYN, S; CASTILLO ANGEL, LEANO A DEL (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1968)
A single specimen of D chelydrae obtained from the small intestine of Chrysemis ornata differs from Stunkard's material in the slight development of the auricular papillae of the oral sucker, the shape of the ovary and size of the eggs
REV GASTROENTEROL
Keywords: STUDY, DIGESTIVE, CAPACITY, STOMACH, PHYSIOCHEMICAL, METHODS; CIENCIAS MEDICAS; OTRAS ESPECIALIDADES MEDICAS (ESPECIFICAR); MEDICINA BIOQUIMICA